Assessment of nurses' workplace silence behaviour motives: A cross-sectional study - Hanadi Mohammed Alhojairi; Naglaa Abdelaziz Mahmoud Elseesy; Sabah Mahmoud Mahran; Maram Ahmed Banakhar; Fatmah Alsharif (Elsevier, 2024)
Objectives: The motives that lead to nurses' workplace silence behaviour are essential to understand, as the failure to voice their concerns and maintain silence may cause various adverse outcomes, including burnout, turnover, job dissatisfaction, low productivity, and mental and moral distress. This study aimed to identify the level and influencing motives of the workplace silence behaviour among nurses at the National Guard Hospital in Madinah. Methods: A descriptive cross-sectional survey was conducted in January and February 2023. The participants completed a questionnaire with two parts: the sociodemographic data form and the Workplace Silence Behavior Nursing Motives Scale. Data analysis was performed by descriptive statistics and the chi-square test. Results: The overall level for all workplace silence behavior motives is moderate (3.29 ± 0.69), with Avoidance Motives dimension receiving the highest scores (3.62 ± 0.75) and Organization-Oriented Motives dimension receiving the lowest (3.15 ± 0.86). Chi-square test showed that Saudi nationality (χ2 = 0.015, P = 0.019) and monthly income (χ2 = 0.045, P = 0.013) are factors in high-moderate levels of silence behaviour. Conclusions: The overall level of workplace silence behaviour motives was found to be moderate, nurses have higher monthly salaries and non-Saudi nationals tend to have higher levels of workplace silence behaviour motives. The study results provide a reference for nursing managers to pay attention to nurses' workplace silence behavior and take corresponding intervention measures.